ICT Engagement and Digital Competence of Preservice English Teachers - Radiamoda, Al-Farouk Abdul Rahman; Ngo, Cristy Grace; Budadong, Degrace; Obiena, Chary Mae (International Journal Corner of Educational Research, 2024)
The study on ICT Engagement and Digital Competence of Preservice English Teachers was a descriptive correlational study conducted among 103 preservice English teachers at the University of Mindanao-Matina Campus, Davao City. This study aimed to identify the levels of ICT engagement and digital competence of preservice English teachers and examine the prevalent relationship between the variables. In gathering the data, this study adopted questionnaires and sampled the total population. The data collected were analyzed using mean, standard deviation, and Pearson's r correlation. Based on the findings, the preservice English teachers have a high level of ICT engagement and a very high level of digital competence. Moreover, the correlation between the variables is moderate, positive, and direct with r-value of 0.427, which suggests that ICT engagement is a construct of digital competence—the more regulated to engage in ICT a person is, the more competent they would become in using ICT. Moreover, the results specify that ICT-related training and support given to language teachers must revolve around troubleshooting digital issues and digital content creation. This study, as a whole, further explored, quantified, and discussed emerging interests in the role of technology in language education, addressing its empirical gap.